Understand the effect of the confinedtrifluoromethane sulfonate (OTf−) anions by the adjacent MXene nanosheets on oriented design of Zn ion storage - Liu, Xin; Du, Mingdong; Zheng, Shunri; Tan, Kar Ban; Zhao, Cuimei; Li, Junyan; Gu, Qinhua; Han, Wenjuan; Xu, Shichong; Lu, Ming; Li, Haibo; Zhang, Bingsen (Elsevier, 2024)
Ion pre-intercalation regulating the tunnel structure of electrode materials accelerates Zn2+ insertion kinetics to realize a high energy storage contribution of Zn-ion batteries. However, electrostatic interaction induced by the pre-intercalated cation and multivalent Zn2+ ions hinders the insertion of Zn2+/H+. In order to retain the negative interlayer surface, herein, OTf− anions were intercalated into the confined spacing by MXene via an electrochemical-driven method. Without changing the potential state of the interlayer spacings, OTf− anion induced a regulated interlayer distance, and a higher oxidation state of V based on the space occupation and the electron transfer mechanism. Consequently, the zinc ion storage capacity of V2CTx MXene increases from 125.2 to 288.7 mAh/g at 0.5 A/g. Interestingly, the negatively charged MXene surface was still intact, which presents lower diffusion barriers of the Zn2+ ions. The merits of anion pre-intercalation are highlighted and provide new insights into the ion storage function-oriented design of MXene.